Hartree-Fock and Density Functional Studies on Vibrational Frequencies of 6-Hydroxyquinoline - Arici, K.; Koksal, H. (Asian Journal of Chemistry, 2010)
The vibrational frequency of 6-hydroxyquinoline in the ground state have been calculated by using Hartree-Fock and density functional methods (B3LYP, BLYP and B3PW91) with 6-31G** as the basis set. Comparison of observed fundamental vibrational frequencies of 6-hydroxyquinoline and calculated results by Hartree-Fock and density functional methods indicates that these methods give good results for molecular vibrational problems. Hartree-Fock method calculated vibrational frequencies of the lowest energy conformer are in good agreement with those observed experimentally.